(untitled) (Journal of human and social sciences, 2022)
Technical and vocational education plays a vital role in human development by providing qualified professionals who meet the needs of both public and private sectors. In Libya, a mismatch exists between the outputs of technical education and the requirements of the labor market, leading to rising unemployment among graduates. This study explores the role of practical applications and graduation projects in bridging this gap by equipping students with technical, analytical, and soft skills aligned with market demands. Using a purposive sample from technical institutions in Benghazi, the research identifies challenges facing graduates in securing jobs and emphasizes the importance of aligning educational outcomes with labor market needs. The study concludes with recommendations to enhance the effectiveness of technical education in reducing unemployment and supporting sustainable development in Libya.